Mast Cells Regulate CD4+ T Cell Differentiation in Absence of Antigen Presentation. (July 2018) - Biefer, Hector Rodriguez Cetina; Heinbokel, Timm; Uehara, Hirofumi; Camacho, Virginia; Koduru, Suresh; El Fatimy, Rachid; Ghiran, Ionita; Trachtenberg, Alexander J; de la Fuente, Miguel A; Azuma, Haruhito; Akbari, Omid; Vasudevan, Anju; et al.
Abstract : Given their unique capacity for antigen uptake, processing, and presentation, antigen presenting cells (APCs) are critical for initiating and regulating innate and adaptive immune responses. Using bone marrow-derived mast cells and mast cell (MC) deficient mice, our in vivo and in vitro findings indicate that following NAD + administration MCs, exclusively, promote CD4 + T-cell differentiation, both in absence of antigen and independently of major APCs. Moreover, we found that MCs mediated CD4 + T-cell differentiation independently of MHC-II and TCR signaling machinery. Although treatment with NAD + resulted in a decreased MHC-II expression on CD11c + cells, MC-mediated CD4 + T-cell differentiation rendered mice resistant to lethal doses of Listeria monocytogenes. Collectively, our study unravels a novel cellular and molecular pathway that regulates innate and adaptive immunity via MCs and may pave the way for novel therapeutic approaches in the context of immunodeficiencies and antimicrobial resistance.